The #1 lawyer eaudiobook - Patterson, James (2024)
Biloxi's best criminal defense attorney has never lost a case. Then his client's beautiful wife is murdered, and America's #1 lawyer suddenly becomes its #1 suspect. Stafford Lee Penney is a small-town lawyer with a big-time reputation for winning every case he tries. In his sharp suits and polished Oxford shoes, Penney is Biloxi, Mississippi's #1 Lawyer and top local celebrity. Just as Penney notches his latest courtroom victory, his wife is scandalously killed. He spirals into a legal and personal losing streak, damaging his reputation and ruining his career. That's when Penney makes a bold decision. He stops trading on his power-lawyer identity and creates a new one: lawyer lifeguard. Moonlighting at the beach, showing up to court in flip-flops, mentoring a law student, the new Penney is at first unrecognizable. It's said that a lawyer who represents himself has a fool for a client. But when Penney is accused of murder, the #1 Lawyer will find a way to triumph.